Characteristics of mental health service use of Brazilian children using routine health records - Araujo, Jacyra; da Silva Rodrigues, Elisângela; Castro-de-Araujo, Luis Fernando Silva; Machado, Daiane Borges; Barreto, Maurício L (International Journal of Population Data Science, 2022)
Background To investigate the clinical epidemiological characteristics of a large data set of visits to outpatient children mental health services in Brazil, as well as to identify relevant relationships between age, sex and three common mental disorders in childhood: pervasive developmental disorders, ADHD and mild depressive disorders. Methods We extracted data from a public repository, DATASUS, regarding child outpatient mental health services in Brazil, from 2008 to 2012. We performed an analysis of the number of visits per inhabitant and inferential analyses with logistic regressions for ADHD (F90.0), Pervasive Developmental Disorders (F84.0-F84.9), and Mild Depressive Episode (F32.0) as outcomes, controlling for age, year of the visit, number of new CAPSI stratified by region. Findings Attention-deficit hyperactivity disorder (ADHD) was the most common condition identified across the country. The analyses by region showed a high number of visits due to mental retardation in the Northeast and depressive episodes in the South. Regressions showed that older children are less likely to visit outpatient services with a diagnosis of ADHD (F90.0). Conclusions Our analysis shows the conditions which cause the most burden to the child psychiatry outpatient centers in Brazil and relevant differences between regions. This information has immediate use for the training of staff and allocation of resources in each region. For collaborations please contact: Email: jacyra.paiva@fiocruz.brFor collaborations please contact: Email: jacyra.paiva@fiocruz.br